2021
DOI: 10.3389/fnins.2021.711074
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds May Be Less Detectable by Susceptibility Weighted Imaging MRI From 24 to 72 Hours After Traumatic Brain Injury

Abstract: Purpose: A former rodent study showed that cerebral traumatic microbleeds (TMBs) may temporarily become invisible shortly after injury when detected by susceptibility weighted imaging (SWI). The present study aims to validate this phenomenon in human SWI.Methods: In this retrospective study, 46 traumatic brain injury (TBI) patients in various forms of severity were included and willingly complied with our strict selection criteria. Clinical parameters potentially affecting TMB count, Rotterdam and Marshall CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Imaging time is relevant for optimizing the prognostic utility of SWI. More specific, due to the biophysical properties of microbleeds, they become isointense to the white matter and temporarily less detectable at 24–72 h following injury [45].…”
Section: Resultsmentioning
confidence: 99%
“…Imaging time is relevant for optimizing the prognostic utility of SWI. More specific, due to the biophysical properties of microbleeds, they become isointense to the white matter and temporarily less detectable at 24–72 h following injury [45].…”
Section: Resultsmentioning
confidence: 99%
“…Greater overall and frontal SWI volumes were related to the severity of TBI [ 31 ]. In another study, researchers evaluated the utility of SWI in a cohort of active military personnel who had suffered mild TBIs (mTBIs) during duty and found that SWI was markedly superior to FLAIR MRI in highlighting cerebral abnormalities comprising white matter hyperintensities [ 26 ]. In another study involving 147 subjects from the military who had sustained TBIs, SWI combined with a multi-scale vessel enhancement filter resulted in significantly better discrimination of venous volumes across all brain regions in the patients than in the controls, which effectively helped characterize chronic pathological changes related to iron deposition and astroglial scarring [ 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lesion volume detected by SWI correlates closely with injury severity and neurological function, and SWI is able to identify a much higher number of hemorrhagic lesions compared to gradient–echo sequences, which helps optimize prognosis and ongoing management decisions. In contrast to SWI, the sensitivity of MRI to TBI characteristics may temporarily be lower 24–72 h after an injury [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the biophysical properties of microbleeds, SWI is less sensitive to hyperacute bleeding (Környei et al, 2021). SWI showed that the sensitivity of traumatic microbleeds was positively correlated with the severity of injury (Trifan et al, 2017), and traumatic microbleeds were not detected in some mild patients (Toth et al, 2013).…”
Section: Susceptibility-weighted Imagingmentioning
confidence: 99%